Identità, valori, cultura - Paolicchi, Piero (SocietàMutamentoPolitica, 2013)
“Scientific” psychology, after great apparent successes, didn’t seems able to account for qualifying features of the human mind and action like those implied in the concept of identity. On the ground of contributions kept out of psychology’s mainstream, like Mead’s symbolic interactionism and Vigotsky’s action theory, some psychological theories were developed in which, on the contrary, identity stays as the essential feature of human beings embedded in historical contexts, but playing an active role inside them. Thus identity becomes a sort of litmus paper for any psychological theory, and not only opens new research directions, but also suggests ways for coming back critically onto psychology’s method and object and for reopening the fruitful exchanges of its beginnings with the other human sciences.